Impacts of the COVID-19 pandemic on German golf - a comparison between club-owned and commercial golf clubs - Christopher Huth; Falk Billion (Nicolaus Copernicus University in Toruń, 2022)
The COVID-19 pandemic turned the international sports world upside down almost overnight. Both professional and popular sports are suffering from the pandemic in equal measure. Sports clubs, which have to bear high fixed costs, are particularly affected. This also includes golf clubs. A primary empirical survey of German golf clubs shows that although the short term - during the lockdown - economic consequences were severe, especially for commercial golf clubs, the 2020 season can be considered successful. This could be an increased interest in exercise in nature and higher health awareness among the population. It is now crucial that golf clubs and associations focus even more intensely on nature (experiences) and health and develop them strategically.